2007
DOI: 10.1213/01.ane.0000255171.94527.c7
|View full text |Cite
|
Sign up to set email alerts
|

Pressures Exerted by Endobronchial Devices

Abstract: A transmitted pressure <30 mm Hg has been recommended to avoid mucosal injury. Our study shows that at clinically relevant cuff volumes, the pressures exerted by the cuffs do not exceed the recommended safe limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 8 publications
2
23
0
1
Order By: Relevance
“…Pressures exerted by the BB cuffs ranged from 39 to 194 mmHg. At intra-cuff volumes required to create a seal to 25 cmH 2 O positive pressure, the pressures exerted by the cuffs of all the devices were less than 30 mmHg [10]. In the present study we found that average cuff pressures were 39.79 ± 4 mmHg on the left side and 84.6 ± 5 mmHg on the right side, respectively.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Pressures exerted by the BB cuffs ranged from 39 to 194 mmHg. At intra-cuff volumes required to create a seal to 25 cmH 2 O positive pressure, the pressures exerted by the cuffs of all the devices were less than 30 mmHg [10]. In the present study we found that average cuff pressures were 39.79 ± 4 mmHg on the left side and 84.6 ± 5 mmHg on the right side, respectively.…”
Section: Discussionsupporting
confidence: 43%
“…In the present study we found that average cuff pressures were 39.79 ± 4 mmHg on the left side and 84.6 ± 5 mmHg on the right side, respectively. Taking into consideration that pressures exerted by the cuffs on the tracheal wall usually correspond to 10-20% of the cuff pressures [10], it may be estimated that in our series they correspond to 4-8 and 8.5-16 mmHg, which is far below the critical perfusion pressure of the bronchial wall (30 mmHg). The pressures exerted by the cuffs on the tracheal wall could be affected by the elasticity of cuff materials, and the relationship of the diameters between the cuff and the bronchus; thus, we need some basic research to prove our hypothesis for the EZblocker.…”
Section: Discussionmentioning
confidence: 55%
“…This is much above the recommended maximal intracuff pressure of 30 cm H 2 O for endotracheal tubes. 25 However, Roscoe and colleagues 25 demonstrated that at intracuff volumes needed to create a seal to a positive pressure of 25 cm H 2 O, the transmitted pressure are less than 30 cm H 2 O. Thus, only a small fraction is transmitted to the bronchial wall.…”
Section: A Comparison Between Dlt and Ezbmentioning
confidence: 99%
“…BB'ler yüksek volümlü -düşük basınçlı kaflara sahip olsalar da yapılan bir çalışmada kaf basınçlarının 160 mmHg'ya kadar çıktığı ancak balonun elastik geri çekilme özelliğinden dolayı bu basıncın yalnızca % 10-20 kadarının bronş mukozasına yansıdığı belirtilmiştir [26] . Bu konuyla ilgili çok fazla sayıda çalışma bulunmamaktadır.…”
Section: Bronşial Blokerlerunclassified